Clinical cases of extrapulmonary manifestations in patients with coronavirus disease (COVID-19) - Riabokon, O. V.; Pak, К. А.; Furyk, O. O.; Cherkaskyi, V. V.; Рябоконь, Олена Вячеславівна; Пак, Катерина Анатоліївна; Фурик, Олена Олександрівна; Черкаський, Володимир Васильович (Запорізький державний медичний університет, 2022)
The aim of the work – to provide variants of extrapulmonary manifestations of coronavirus disease (COVID-19) based on the analysis of the relevant course of the disease in adults. Results. The paper presents two clinical cases of coronavirus disease (COVID-19) with the manifestation of extrapulmonary symptoms, which required some individualization of therapy. The first clinical observation showed that in a 56-year-old patient with moderate COVID-19, the development of oxygen dependence on the 8th day of the disease was combined with the manifestation of extrapulmonary symptoms in the form of cutaneous manifestations. Individualization of glucocorticosteroid therapy and endothelioprotective therapy has been shown to be effective in regressing both oxygen dependence and cutaneous vasculitis. The second clinical observation showed that in a 35-year-old patient, moderate COVID-19 without oxygen dependence was accompanied by the development of extrapulmonary manifestations, namely short-lasting diarrheal syndrome, which manifested in the onset of the disease and of the development of orchiepididymitis on the 9th day of illness, which required the appointment of anti-inflammatory therapy. Conclusions. The abovementioned clinical observations of COVID-19 cases show relatively rare cases of SARS-CoV-2- associated extrapulmonary manifestations in patients with moderate disease, but their development necessitated individualization of treatment. Мета роботи – описати варіанти позалегеневих проявів коронавірусної хвороби (COVID-19) на підставі здійсненого аналізу відповідного перебігу хвороби у дорослих. Результати. В роботі наведено два клінічних випадки коронавірусної хвороби (COVID-19) з маніфестацією позалегеневої симптоматики, що потребувала певної індивідуалізації терапії. Перше клінічне спостереження показало, що в пацієнтки віком 56 років із середньотяжким перебігом COVID-19 виникнення кисневої залежності на 8 добу хвороби поєднувалося з маніфестацією позалегеневої симптоматики – шкірними проявами. Виявили, що індивідуалізація лікування з призначенням глюкокортикостероїдів та ендотеліопротективної терапії виявилась ефективною щодо регресу і кисневої залежності, і шкірних проявів васкуліту. У другому клінічному випадку показано, як у пацієнта віком 35 років середньотяжкий перебіг COVID-19 без кисневої залежності супроводжувався виникненням позалегеневих проявів: ураженням кишечника, що проявилося короткочасним діарейним синдромом у дебюті захворювання, та розвитком орхоепідидиміту на 9 день хвороби, яке потребувало призначення протизапальної терапії. Висновки. Клінічні спостереження випадків COVID-19, що описали, показують відносно рідкісні випадки виникнення SARS-CoV-2-асоційованих позалегеневих проявів, які виникли у пацієнтів із середньотяжким перебігом хвороби, проте їх розвиток зумовив необхідність індивідуалізації лікування.
Клінічні випадки позалегеневих проявів у хворих на коронавірусну хворобу (COVID-19)
Riabokon O. V. - ORCID ID: 0000-0002-7394-4649; Pak K. A. - ORCID ID: 0000-0002-2286-6919; Furyk O. O. - ORCID ID: 0000-0002-5196-7698; Cherkaskyi V. V. - ORCID ID: 0000-0003-2959-8803.
Keywords: coronavirus disease COVID-19; viral infection; extrapulmonary manifestations; treatment; коронавірусна хвороба COVID-19; вірусна інфекція; позалегеневі прояви; лікування